ANALISIS PEMBATASAN JUMLAH PEMBUATAN AKTA PERHARI PASCA KELUARNYA PERATURAN DEWAN KEHORMATAN PUSAT IKATAN NOTARIS INDONESIA NOMOR 1 TAHUN 2017 - SHALLY SHALLY (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Rudy Haposan3. Faisal Akbar Nasution A Notary is appointed by the government in order to serve people. One of the regulations on supervision and guidance especially by the Honorary Council as stipulated Article 4 Paragraph 16 of the Notarial Ethics code that is realized bt the regulation of the Central Honorary Council of the Indonesia Notarial Asscociations No.1/2017 that the limit of fairness in deed per day is 20 (twenty) deeds. Based on the result of the research is still found that this regulation was violated.Keyword : Notary, Honorary Council, the Supervisiory Council